Student Feedback as a Mediator of Ease and Motivation in Math Playground Game Learning on the Learning Success of Elementary School Students - Masraria; Pajarianto, Hadi; Ching Yang, Chen; Masnur (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to examine how perceived ease of use and motivation to use the Math Playground learning game influence student feedback and learning success among elementary school students in Indonesia. A quantitative survey approach was employed, involving 160 students selected through convenience sampling, all of whom had prior experience using the game in mathematics learning activities. Data were analyzed using covariance-based Structural Equation Modeling (CB-SEM) with AMOS to test direct and indirect relationships among variables and to examine the structural mechanisms within the proposed research framework. The results indicate that perceived ease of use does not have a significant direct effect on learning success; however, it positively and significantly influences student feedback. In contrast, motivation to use the learning game has a positive and significant effect on both student feedback and learning success. Furthermore, student feedback significantly affects learning success and partially mediates the relationship between motivation and learning success. These findings suggest that while system usability enhances students’ comfort and responsiveness, psychological factors, particularly motivation, play a more decisive role in improving academic outcomes. The study highlights the importance of fostering students’ learning motivation when integrating digital games into classroom instruction. Additionally, educational technology developers should prioritize motivational design elements and meaningful feedback systems rather than focusing solely on technical simplicity. Overall, this research contributes empirical evidence to the game-based learning literature by clarifying the mediating role of student feedback within elementary education in the Indonesian context.